2011
DOI: 10.1371/journal.pone.0022838
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-96 Directly Inhibits γ-Globin Expression in Human Erythropoiesis

Abstract: Fetal hemoglobin, HbF (α2γ2), is the main hemoglobin synthesized up to birth, but it subsequently declines and adult hemoglobin, HbA (α2β2), becomes predominant. Several studies have indicated that expression of the HbF subunit γ-globin might be regulated post-transcriptionally. This could be confered by ∼22-nucleotide long microRNAs that associate with argonaute proteins to specifically target γ-globin mRNAs and inhibit protein expression. Indeed, applying immunopurifications, we found that γ-globin mRNA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 56 publications
2
82
1
Order By: Relevance
“…In vitro studies established that miR-96 directly targets the ORF of g-globin to mediate gene silencing. 14 Furthermore, the LIN28B/let-7 interaction holds great promise for supporting the design of let-7 antagomirs and/or LIN28B expression systems to induce HbF in the erythroblasts of sickle cell patients. 15,37 A limited number of miRNA studies have been conducted in humans to elucidate mechanisms of HbF expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies established that miR-96 directly targets the ORF of g-globin to mediate gene silencing. 14 Furthermore, the LIN28B/let-7 interaction holds great promise for supporting the design of let-7 antagomirs and/or LIN28B expression systems to induce HbF in the erythroblasts of sickle cell patients. 15,37 A limited number of miRNA studies have been conducted in humans to elucidate mechanisms of HbF expression.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA (miRNA) molecules are small endogenous non-coding RNAs that regulate gene expression by interfering with mRNA translation or disrupting its stability to promote degradation. Azzouzi et al 14 demonstrated that g-globin mRNA is bound by an argonaute 2-containing miRNA-induced silencing complex in reticulocytes isolated from adults with an average 0.5% HbF when compared to umbilical cord blood reticulocytes with >90% HbF. miRNA screening studies identified miR-96 which targets the open reading frame (ORF) of g-globin mRNA as a mechanism of gene silencing.…”
Section: Introductionmentioning
confidence: 99%
“…However, miRNA regulation of ␤-like globin genes is underexplored, in part due to the short 3= UTRs of globin genes. Very few miRNAs targeting globin have identified, except for miR-96, which was shown to directly suppress the ␥-globin gene by binding to its CDS region (19). In addition, a few reports focus on miRNAs indirectly regulating globin genes through targeting of known transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other transcription factors, such as NF-E2 (8,9), GATA-1 (10), FOG (11), Sox6 (12), NF-E3 (13), SP1 (14,15), KLF3/BKLF (16,17), TR2, and TR4 (18), are involved in the control of ␤-like globin gene expression. Although these studies represent significant advances in the understanding of ␤-like globin gene regulation at the transcriptional level, only a few microRNAs (miRNAs) have been found to be regulators of the ␤-like globin locus (19,20,21). miRNAs are endogenous, approximately 22-nucleotide (nt) RNAs that play important regulatory roles at the posttranscriptional level in animals and plants by targeting mRNAs for cleavage or translational repression (22,23,24).…”
mentioning
confidence: 99%
“…24 Recently, miR-96 expression in reticulocytes was demonstrated to increase during human ontogeny, 24 and miR-96 knockdown resulted in increased g-globin expression in human erythroblasts. 41 However, the miR-96 effects on HbF expression in mature erythroid cells were not defined. Three erythroid miRNAs that are not developmentally regulated (miR-451, miR-144, and miR-142) were tested as controls.…”
mentioning
confidence: 99%